(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The goal of this paper is to determine which criteria for sales managers the most important when are choosing a candidate for the position of salesperson. That will allow students who want to build their career in sales to prepare beforehand for what will be required of them, thereby helping companies in the future hire salespersons who will be better prepared for the challenges which this profession brings. The research was conducted through a questionnaire distributed to sales managers at companies in the Republic of Macedonia. Each one of them assesses the importance of certain criteria related to formal and informal education, knowledge of foreign languages, skills, personal characteristics, etc., by using a given scale. The obtained results are presented and analyzed. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.